2010
DOI: 10.1091/mbc.e10-02-0119
|View full text |Cite
|
Sign up to set email alerts
|

AspergillusRabBRab5Integrates Acquisition of Degradative Identity with the Long Distance Movement of Early Endosomes

Abstract: Of the two Aspergillus early endosomal Rab5 paralogues, RabB recruits, in its GTP conformation, Vps19, Vps45, and Vps34, and the CORVET complex and couples acquisition of PI(3)P degradative identity with the long-distance movement of early endosomes. RabA also recruits CORVET, albeit less efficiently. The simultaneous loss of RabA and RabB is lethal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(164 citation statements)
references
References 64 publications
4
158
1
Order By: Relevance
“…It later turned out that the four proteins function together along the endocytic pathway also in metazoan cells (Peterson and Emr, 2001;Richardson et al, 2004;Sriram et al, 2003;Rieder and Emr, 1997;Srivastava et al, 2000), although they are part of two complexes in yeast -CORVET (Peplowska et al, 2007) and HOPS Wurmser et al, 2000) ( Fig. 2A) which was nicely confirmed in the fungus Aspergillus nidulans (Abenza et al, 2010;Abenza et al, 2012). In agreement with a shared function of the four class C proteins, deletion of the remaining two subunits of either complex is less dramatic (Horazdovsky et al, 1996;Markgraf et al, 2009;Nakamura et al, 1997;Raymond et al, 1992;Raymond et al, 1990;Wada et al, 1992), suggesting that there is some functional redundancy of HOPS and CORVET within the endocytic pathway.…”
Section: Box 1 the Functions Of Rab5 And Rab7 Within The Endolysosommentioning
confidence: 86%
See 3 more Smart Citations
“…It later turned out that the four proteins function together along the endocytic pathway also in metazoan cells (Peterson and Emr, 2001;Richardson et al, 2004;Sriram et al, 2003;Rieder and Emr, 1997;Srivastava et al, 2000), although they are part of two complexes in yeast -CORVET (Peplowska et al, 2007) and HOPS Wurmser et al, 2000) ( Fig. 2A) which was nicely confirmed in the fungus Aspergillus nidulans (Abenza et al, 2010;Abenza et al, 2012). In agreement with a shared function of the four class C proteins, deletion of the remaining two subunits of either complex is less dramatic (Horazdovsky et al, 1996;Markgraf et al, 2009;Nakamura et al, 1997;Raymond et al, 1992;Raymond et al, 1990;Wada et al, 1992), suggesting that there is some functional redundancy of HOPS and CORVET within the endocytic pathway.…”
Section: Box 1 the Functions Of Rab5 And Rab7 Within The Endolysosommentioning
confidence: 86%
“…In agreement with a shared function of the four class C proteins, deletion of the remaining two subunits of either complex is less dramatic (Horazdovsky et al, 1996;Markgraf et al, 2009;Nakamura et al, 1997;Raymond et al, 1992;Raymond et al, 1990;Wada et al, 1992), suggesting that there is some functional redundancy of HOPS and CORVET within the endocytic pathway. In addition to the four shared class C proteins, CORVET contains two Rab5-binding subunits, Vps3 and Vps8, whereas HOPS has instead the Rab7-binding subunits Vps39 and Vps41 (also known as Vam6 and Vam2) (Abenza et al, 2010;Abenza et al, 2012;Markgraf et al, 2009;Peplowska et al, 2007;Price et al, 2000;Seals et al, 2000;Wurmser et al, 2000). The similarity between HOPS and CORVET suggests that intermediate complexes also exist, and indeed a complex of low abundance can be isolated that consists of the class C subunits, plus HOPS Vps41 and CORVET Vps3 Peplowska et al, 2007) (Fig.…”
Section: Box 1 the Functions Of Rab5 And Rab7 Within The Endolysosommentioning
confidence: 99%
See 2 more Smart Citations
“…S2C). Previous studies have shown that Rab7 is involved in the fusion of lysosomes by binding to the homotypic fusion and protein sorting (HOPS) complex (Wurmser et al, 2000;Abenza et al, 2010Abenza et al, , 2012Ostrowicz et al, 2010;Balderhaar and Ungermann, 2013). Thus, it is possible that rapsyn also promotes the clustering of Rab7 either directly or indirectly through its association with the Rabring 7 effector as implied by its colocalization with Rab7.…”
Section: Discussionmentioning
confidence: 99%